Case Report: A Domestic Sponge Brush Used to Clean a Milk Feeding Bottle: The Source of Neonatal Meningitis Caused by Pseudomonas aeruginosa - Shinsuke Mizuno; Sayaka Matsuzaki; Koji Yokoyama; Keigo Hamahata; Akira Yoshida (Frontiers Media S.A., 2021)
Pseudomonas aeruginosa is a relatively rare cause of neonatal meningitis, and most patients have serious underlying diseases, prematurity, immunodeficiency, or anatomical abnormalities. We report the case of a 7-day-old girl with meningitis caused by P. aeruginosa. She was born full-term and had no immunodeficiency or anatomical abnormalities as far as our investigation ascertained. Through the use of anti-Pseudomonas antibiotics, she recovered without any complications other than a slight hearing disability revealed by audiology testing. P. aeruginosa was also isolated from a domestic sponge brush used to clean her milk bottle. Physicians should consider P. aeruginosa as a possible pathogen of neonatal meningitis even in full-term infants with no immunodeficiency or anatomical abnormalities. Physicians should give advice concerning appropriate hygiene practices to be applied to the neonate's environment.